Association of ABCC2 polymorphism with clopidogrel response in Chinese patients undergoing percutaneous coronary intervention - Chen, Lida; Zheng, Chao; Hao, Mengmeng; Gao, Peng; Zhao, Meimei; Cao, Yongtong; Ma, Liang (Frontiers in Pharmacology, 2022)
Aim: In this study, we investigated the association between ABCC2 polymorphism and clopidogrel response as well as the associated hypothetical mechanism. Methods: Chinese patients (213) with coronary artery disease (CAD) who underwent percutaneous coronary intervention (PCI) and received clopidogrel were recruited. Thereafter, their ADP-induced platelet inhibition rates (PAIR%) were determined via thromboelastometry. Further, the single-nucleotide polymorphisms (SNPs) of ABCC2 were genotyped using high-resolution melting curve (HRM)-PCR, while CYP2C19*2 and *3 polymorphisms were genotyped via real-time PCR. Results: The allele frequencies of ABCC2 rs717620 were 74.88 and 25.12% for the C and T alleles, respectively. Further, ABCC2 rs717620 TT carriers exhibited significantly higher PAIR% values (72.60 ± 27.69) than both CT (61.44 ± 23.65) and CC carriers (52.72 ± 21.99) (p = 0.047 and p = 0.001, respectively), and ABCC2 rs717620 CT carriers showed significantly higher mean PAIR% values than ABCC2 rs717620 CC carriers (p = 0.011). However, the PAIR% values corresponding to ABCC2 rs2273697 and ABCC2 rs3740066 carriers were not different. Additionally, CYP2C19*2 AA carriers presented significantly lower PAIR% values than CYP2C19*2 GA (p = 0.015) and GG (p = 0.003) carriers, and CYP2C19*3 GA carriers also presented significantly lower PAIR% values than CYP2C19*3 GG carriers (p = 0.041). In patients with CYP2C19 extensive metabolizers (EM), ABCC2 rs717620 TT carriers showed significantly higher PAIR% values (89.77 ± 9.73) than CT (76.76 ± 26.00) and CC carriers (74.09 ± 25.29) (p = 0.040 and p = 0.009, respectively). In patients with CYP2C19 poor metabolizers (PM), ABCC2 rs717620 CC carriers showed significantly lower PAIR% values (51.72 ± 25.78) than CT carriers (75.37 ± 23.57) (p = 0.043). Furthermore, after adjusting for confounding factors, ABCC2 rs717620 was identified as a strong predictor of clopidogrel hyperreactivity. Conclusion: We proposed a new target, ABCC2 rs717620, in the efflux pathway that affects individual responses to clopidogrel. The TT allele of ABCC2 rs717620 was also identified as an independent risk factor for clopidogrel hyperreactivity, and CYP2C19*2 and *3 showed association with an increased risk for clopidogrel resistance. Additionally, ABCC2 rs717620 may affect individual responses to clopidogrel via post-transcriptional regulation and interaction with CYP2C19. These findings provide new insights that may guide the accurate use of clopidogrel.